Soberania popular na crise do século XIV e o surgimento do conceito forte de soberania: Marsílio de Pádua, Guilherme de Ockham e Jean Bodin - De Matos, Saulo (2016)
This article analyzes the significance of the concepts “sovereignty” and “popular sovereignty” regarding the construction of modern law. Modern law isdefined in this study as a language of subjective rights (claim, liberty, power and immunity) and therefore has a nomological and authoritative character. The shift from low Middle-age to the beginning of Modernity seems to be the decisive period to understand the construction of modern law, due to the reception of Aristotle’s political writings and Roman law, aside from the rejection of strong or thomist realism. In this sense, three works are analyzed: Marsilio of Padua “DefensorPacis”, William of Ockham “Breviloquium de Principatur Tyrannico” and Jean Bodin “Six Books of the Commonwealth”. The results seem to address that popular sovereignty as a foundation for legal language is in direct opposition to the acceptance of the strong concept of sovereignty, as stated by Bodin.